Hubungan Kualitas Hidup Lansia dengan Food Intake di Panti Sosial Tresna Werdha Ina Kaka Ambon - Angeline Pieter; Desi Desi; Theresia Pratiwi E Sanubari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
AbstractThe decline in the functioning of the body's systems in the elderly as they get older can change certain nutritional aspects such as the sense of smell and taste, the ability to chew and swallow and the digestive function makes food uncomfortable and the elderly's appetite decreases . The decrease in food intake certainly affects the quality of life of the elderly. Food intake is one of the important factors to meet the needs of good nutritional intake. Elderly with high quality of life can cover all existing domains and also a good food intake for the changes experienced by the elderly. So that it becomes the basis of the importance of improving the quality of life and food intake of the elderly. The study was conducted to explore the relationship between quality of life and food intake at the Tresna Werdha Inakaka Social Home in Ambon. Research using quantitative methods with descriptive correlation design. The respondents involved were the elderly at the Tresna Werdha Ina Kaka Social Home, Ambon. Sampling using purposive sampling technique with respondents as many as 36 elderly. The data were processed using the excel program and then tested using the SPSS program to determine the relationship between variables. Data analysis using SPSS 20 correlation test or correlation using Pearson Product Moment with a significance level of 0.05. The results showed that there was a relationship between variables in quality of life and food intake, with a moderate degree of correlation that led to a positive direction (r = 0.502; p = 0.002; p <0.05). Based on the results of the study, it can be concluded that in the Tresna Werdha Ina Kaka Social Home, the quality of life and food intake have a moderate relationship, the higher the quality of life the better the food intake for the elderly.Keywords: Elderly, Quality of Life, Food Intake